Criminal Liability for Hoax Spreaders: A Study of Defamation Offenses and ITE Laws - Muhammad Junaidi; Samsir Samsir; Achmad Yusuf (Journal of Strafvordering Indonesian, 2025)
The widespread dissemination of hoaxes and the expanding criminalization of defamation in digital spaces illustrate that challenges within Indonesia’s cyberlaw regime stem not only from the normative wording of the ITE Law but also from law enforcement practices that fail to accommodate the realities of digital communication. This study examines criminal liability for hoax disseminators and defamation offenses under the ITE Law by integrating the Criminal Code (Law 1/2023), the first amendment to the ITE Law (Law 19/2016), and the most recent amendment (Law 1/2024). Employing normative legal research through statutory, conceptual, and case approaches, the study finds that hoax-related criminal liability raises substantial mens rea concerns, particularly because digital virality often results from impulsive user behavior driven by platform algorithms. Meanwhile, defamation provisions under the ITE Law retain a conduct-based orientation, expanding criminal liability through broadly framed elements such as “distributing,” “transmitting,” and “making accessible.” Limited digital forensic capacity, subjective interpretation by law enforcement, and weak application of public-interest safeguards contribute to excessive criminalization of both hoax disseminators and legitimate criticism. The study concludes that the effectiveness of the ITE Law requires harmonization with culpability principles under the Criminal Code, strengthened institutional capacity, the adoption of objective standards, and a clear restriction of criminal sanctions as ultimum remedium to ensure that public order and reputation protections do not undermine democ.